2016
DOI: 10.1002/2015jc011576
|View full text |Cite
|
Sign up to set email alerts
|

Swell impact on wind stress and atmospheric mixing in a regional coupled atmosphere‐wave model

Abstract: Over the ocean, the atmospheric turbulence can be significantly affected by swell waves.Change in the atmospheric turbulence affects the wind stress and atmospheric mixing over swell waves. In this study, the influence of swell on atmospheric mixing and wind stress is introduced into an atmospherewave-coupled regional climate model, separately and combined. The swell influence on atmospheric mixing is introduced into the atmospheric mixing length formula by adding a swell-induced contribution to the mixing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…These characteristics make swells an indicator of various atmospheric phenomena such as tropical cyclones, distant storms, or even large-scale sea breezes such as those related to monsoons. Swells also have significant impacts on the transport and dispersion of oil plumes within the ocean mixed layer, ocean surface roughness, wind stress, and other things Hwang, 2008;Wu et al, 2016). Because of their substantial energy and good stability, energy production from swell waves has received increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make swells an indicator of various atmospheric phenomena such as tropical cyclones, distant storms, or even large-scale sea breezes such as those related to monsoons. Swells also have significant impacts on the transport and dispersion of oil plumes within the ocean mixed layer, ocean surface roughness, wind stress, and other things Hwang, 2008;Wu et al, 2016). Because of their substantial energy and good stability, energy production from swell waves has received increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…[] investigated how swell‐roughness impacts U 10 with a wave‐atmospheric regional climate model focusing on the European area. Even at such high latitudes, the influences of swell are evident [ Wu et al ., ]. The impact of swell on the climate system needs to be explored and analyzed more deeply.…”
Section: Resultsmentioning
confidence: 99%
“…Observations have shown that surface waves can also drive the wind (Grachev & Fairall, 2001) when remotely generated swells propagate substantially faster than the calm local wind. Inclusion of swell effects on the wind stress and atmosphere mixing has been shown to improve simulated wind speeds (Wu et al, 2016). This makes waves an important factor in mediating the air‐sea momentum transfer.…”
Section: Introductionmentioning
confidence: 99%